Reforming the shadow carceral state - Friedman, Brittany (Theoretical criminology, 2024)
This article examines the repeal of prison pay-to-stay policies in the United States. We process-trace reform efforts in Illinois drawing from novel data retrieved through multiple FOIA requests to state agencies and public records searches. Our analysis reveals how lawmakers who advocated for reforming the shadow carceral state in 2016 and 2019 through repealing prison pay-to-stay repurposed penal logics they had once used punitively in the 1980s and 1990s to enact the same policy—such as protecting taxpayers, fiscal efficiency, and rehabilitation. Our findings advance existing research by suggesting that penal logics are open to interpretation depending on the socioeconomic and historical moment. These contextual factors are also crucial to determining how lawmakers and institutions re-interpret long held penal logics when reforming the shadow carceral state. We argue the ways in which lawmakers strategically operationalize penal logics exemplifies their cultural durability as a resonant means to a political end.